PERAN INTERNATIONAL MONETARY FUND (IMF) DALAM PEMULIHAN PEREKONOMIAN SEYCHELLES TAHUN 2008 - 2013 - INDAH MAISURI; Faisyal Rani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research describes the role of the IMF in Seychelles economic recovery in debt crisis and the economic crisis at the same time. As the recovery effort, Seychelles assisted by IMF agreed to conduct macroeconomic reforms program written in the Letter of Intent (LoI).This study obtained data sources from books,academic journals, official website of IMF and the annual report of the Central Bank of Seychelles as well as several documents such LoI and Paris Club. This study used a liberal paradigm and the role theory and the international organization theory, and national-state level of analysis.This research found that the international organization has an important role in international system besides state actors. The IMF was establised aiming to help countries in trouble with balance of payments and debt crisis such as Seychelles. IMF feels responsible to help Seychelles out of the problem through macro-economic reforms program. Although the program still going but the process indicated to a better changes.Keywords: Debt Crisis, Debt Restructuring, International Monetary Fund, Macroeconomic Reforms Program, Seychelles.